Sibling dynamics and sport expertise. Issue 5 (31st January 2015) - Hopwood, M. J.; Farrow, D.; MacMahon, C.; Baker, J.
Abstract : Family members are known to be highly influential in the development of sport expertise. To date, much of the research in this area has focused on parents, with less known about sibling influences on expertise. This investigation explored associations between sport expertise, sibling characteristics, and sibling participation in sport and physical activity. Athletes representing three skill levels provided details of sibling characteristics and participation in sport and physical activity via the Developmental History of Athletes Questionnaire. Elite athletes were more likely to be later‐born children, while pre‐elite and non‐elite athletes were more likely to be first‐born. Compared with siblings of non‐elite athletes, siblings of elite athletes were more likely to have participated in regular physical activity and were more likely to have participated in sport at the pre‐elite and elite levels. These results suggest siblings may play a key role in sport expertise development.